Local and regional climate variables driving spring phenology of tortricid pests: a 36 year study. (19th December 2018) - Pak, Damie; Biddinger, David; Bjørnstad, Ottar N.
Abstract : 1. Insect phenology is driven by local climate variables, most notably temperature. Increased warming has been linked to advancements in critical phenophases such as the spring flight of reproductive adults in the mid‐Atlantic region of the U.S.A. 2. Local climate is governed by the fluctuations of large‐scale climate oscillations. In the northern hemisphere, both the North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO) control the local autumn and winter severity. Low NAO and AO indices are associated with colder autumns and winters, which can delay spring phenology. 3. In this study, 36 years of data from experimental fruit orchards in Biglerville, Pennsylvania, were used to run partial least‐squares regressions in order to determine the climate variables related to the spring phenology of five tortricid pest species. 4. The phenology of the tortricid pests did not advance, even though there was evidence of warming at the research site. 5. Spring temperatures were found to be the most significant climate variables in determining the timing of the spring flights. However, autumn–winter temperatures were also important. 6. For the NAO and the AO, it was found that these oscillations affected the tortricid moths by influencing autumn–winter conditions. The oscillations of the NAO and AO can obscure long‐term changes in phenology. 7. These findings suggest that the inclusion of large‐scale climate oscillations can provide important insights into how climate conditions can influence insect phenology, and presents an opportunity for improving the ability to forecast spring emergence. Abstract : The phenology of the tortricid moths did not advance, even though there was evidence of warming at the research site. It was found that, in addition to spring conditions, colder autumn–winter temperatures were generally linked to later spring flights. In the mid‐Atlantic, the North Atlantic Oscillation and the Arctic Oscillation govern autumn–winter conditions, which in turn influence the tortricid phenology.